Integrative transcriptome and metabolome analysis reveals the mechanism of fulvic acid alleviating drought stress in oat - Zhu, Shanshan; Mi, Junzhen; Zhao, Baoping; Wang, Zhaoming; Yang, Zhixue; Wang, Mengxin; Liu, Jinghui (Frontiers in Plant Science, 2024)
Drought stress inhibits oat growth and yield. The application of fulvic acid (FA) couldan improve the drought resistance of oats, but the corresponding molecular mechanism of FA-mediated drought resistance of oats remainsis still unclear. Here, we studied the effects of FA on the drought tolerance of oat leaves through physiological, transcriptomic, and metabolomics analyseis, and identified FAinduced genes and metabolites related to drought tolerance. Physiological analysis showed that under drought stress, FA increased the relative water content and chlorophyll contents of oat leaves, enhanced the activity of antioxidant enzymes (SOD, POD, PAL, and CAT and 4CL), inhibited the accumulation of malondialdehyde (MDA), and hydrogen peroxide (H2O2) and dehydroascorbic acid (DHA), reduced the degree of oxidative damage in oat leaves, improved the drought resistance of oats, and promoted the growth of oat plants. Transcriptome and metabolite analyses revealed 652 differentially expressed genes (DEGs) and 571 differentially expressed metabolites (DEMs) in FA-treated oat leaves under drought stress. These DEGs and DEMs are involved in a variety of biological processes, such as phenylspropanoid biosynthesis and glutathione metabolism pathways. In aAdditionallyddition, FA may be involved in regulating the role of DEGs and DEMs in phenylpropanoid biosynthesis and glutathione metabolism under drought stress. In conclusion, our results suggest that FA promotes oat growth under drought stress by attenuating membrane lipid peroxidation and regulating the antioxidant system, phenylpropanoid biosynthesis, and glutathione metabolism pathways in oat leaves. This study provides new insights into the complex mechanisms by which FA improves drought tolerance in crops.